A VAGINAL FIBROMA IN A POMERANIAN BITCH - A CASE REPORT - Suthar, B N; Chaudhary, S R; Nakhashi, H C; Chaudhari, N F; Suthar, D N; Joshi , D V (Indian Journal of Veterinary Sciences and Biotechnology, 2010)
Tumors of vagina and vulva in bitch are rare and account only 2.5-3.0 per cent of the canine tumors (Brodey and Roszel, 1967). The most frequent tumors of vagina and vulva are non-malignant fibroma, leiomyoma or polyps which comprise about 70-80 per cent. The present paper reports a case of vaginal fibroma in a Pomeranian bitch.